Pengaruh Kadar Air Dan Porositas Tanah Terhadap Efisiensi Pemberian Pupuk Pada Tanaman Jagung - Laoli, Monica Lesta Endang Yanti; Halawa, Charles Firson (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Degradation of soil structure in wetlands can significantly affect drainage systems, potentially leading to excess water accumulation and risk of flooding. This research aims to analyze the effect of soil structure degradation on drainage in wetlands by comparing the physical and chemical characteristics of soil in degraded and control locations. Soil sampling was carried out in several locations, and laboratory analysis showed a decrease in porosity, permeability and organic matter content in degraded areas. The results showed that degradation of soil structure had a negative impact on drainage efficiency, leading to higher waterlogging in wetlands. Sustainable management recommendations, such as the application of soil conservation techniques, are proposed to improve soil structural conditions and support the sustainability of wetland ecosystems.